Meningkatkan Kemampuan Membaca Permulaan Melalui Metode Sas (Struktural Analisis Sintetik) Bagi Anak Tunagrahita Ringan - Rohayati, Rohayati; Budi, Setia (Jurnal Penelitian Pendidikan Khusus, 2022)
This study aims to prove whether the SAS method can improve early reading skills in intellectual disability. The research method used is classroom action research which consists of two cycles. With the SAS method, intellectual disability students can read structurally. Based on the results of the study, the ability of children to read at the beginning increased compared to before using the SAS method. This is evident from the results of research using the SAS method to improve early reading skills.